The times they are a-changin’: The evolution of prostate cancer screening practices and beliefs among primary care physicians in Victoria, British Columbia - Spooner, Jesse; Birk, Manjot; Espionsa, Victor; Hoag, Nathan (Canadian Urological Association Journal, 2020)
Introduction: Prostate cancer screening practices remain controversial among primary care practitioners (PCPs). Inconsistent guidelines and publication of large prostate cancer screening trials have failed to provide definitive guidance. This study investigates the evolution of prostate cancer screening practices and beliefs over 12 years, in Victoria, British Columbia. Methods: Questionnaires were delivered to 119 randomly selected PCPs in 2019. Descriptive analysis together with exploratory graphs and Pearson Chi-squared test for independence was calculated. The 2008 data was compared by determining if their value fell within the 2019 data’s 95% confidence interval. Results: Response rate was 69.8% (83/119); 30.1% of PCPs reported regularly screening asymptomatic men with prostate-specific antigen (PSA) testing and 37.3% reported regularly performing digital rectal exam (DRE). The combination of PSA and DRE was the most used (48.2 %) screening modality. Most (73.5%) reported that guidelines influence their screening practices, with the most popular choice being those published by The Canadian Task Force on Preventive Health Care (CTF) (32.5%). Conclusions: The results demonstrate a movement away from prostate cancer screening among PCPs when compared to 2008. PCPs believe that DRE and PSA are less valuable as screening tools and that there is insufficient evidence to support their use. The most used initial screening modality was the combination of PSA/DRE, however, we found a decrease in their use between the two study periods. Clinical guidelines continue to influence PCPs screening practices, but the shift of more PCPs following the CTF guidelines since 2008 has likely led to the reciprocal decrease in prostate cancer screening.